2014
DOI: 10.4172/2165-7386.1000195
|View full text |Cite
|
Sign up to set email alerts
|

Educational Programs for Family Caregivers in Palliative Care: A Literature Review

Abstract: Aim: To analyse the literature about educational programs aimed towards empowering caregivers of patients in palliative care (PC) attending to the conceptual difference between programs and psychosocial interventions. Results: Eight studies were identified and analysed concerning subject matter, measurement instruments, location, results, strategy and duration of the programs. All educational programs addressed issues related to the context of end of life; Program duration ranged from three weeks to two years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…A proper training or education program given to family caregivers can significantly increase their comfort with caregiving roles, assist with closure, and gain caregivers’ confidence (Kwak et al, 2007 ). However, there is a limitation in publications concerning education for family caregivers, suggesting that there may be limited findings to support such studies (Reigada et al, 2014 ). Previous reviews indicate that demographic characteristics, particularly gender, play a significant role in determining the most appropriate setting for educational programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proper training or education program given to family caregivers can significantly increase their comfort with caregiving roles, assist with closure, and gain caregivers’ confidence (Kwak et al, 2007 ). However, there is a limitation in publications concerning education for family caregivers, suggesting that there may be limited findings to support such studies (Reigada et al, 2014 ). Previous reviews indicate that demographic characteristics, particularly gender, play a significant role in determining the most appropriate setting for educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have been conducted to explore interventions that support family caregivers (Ahn et al, 2020 ; Hudson et al, 2010 ; Li et al, 2021 ), including educational interventions (Bilgin & Ozdemir, 2022 ; Phongtankuel et al, 2018 ; Reigada et al, 2014 ). However, these reviews revealed that the majority of evidence was retrieved from HICs, highlighting the need for diversity in information from various ethical, cultural, and economic backgrounds (Ahn et al, 2020 ; Hudson et al, 2010 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, data were verbatim transcribed following each interview. The transcript results were entered into NVivo 12 plus to complete an iterative analysis process (Martins Pereira et al, 2011 ; Reigada et al, 2014 ). Individual interviews were recorded during the online discussion using a Sony digital flash memory voice recorder and phone recorder.…”
Section: Methodsmentioning
confidence: 99%